MAPPADEKKO : STUDI ATAS TRADISI PESTA PANEN DI DESA BIALO KABUPATEN BULUKUMBA - Aulia, Guruh Ryan; Putri, Lindi Aulia (Prodi Tadris Ilmu Pengetahuan Sosial FITK UIN Sumatera Utara Medan, 2025)
This study explores the harvest festival tradition in Bialo Village, Bulukumba Regency, focusing on its origin, process, and cultural meaning. Using a qualitative approach through interviews, observation, and documentation, the research finds that the tradition stems from a local agricultural system emphasizing togetherness and gratitude. The festival includes collective prayers, traditional art performances, and shared meals of harvested crops. For the Bialo community, it is not merely a celebration but a cultural expression that fosters social cohesion and community identity. It also functions as a means to pass down local wisdom and values to younger generations. Amid ongoing modernization, the harvest festival plays a key role in preserving cultural identity and social resilience. It reflects the community's close connection with nature and reinforces the importance of sustaining traditional practices in an ever-changing cultural landscape.